ACID-CATALYZED TRANSFORMATION OF ALPHA-TRIFLUOROMETHANESULFONATES OF GAMMA-LACTONES AND DELTA-LACTONES INTO 2,5-DISUBSTITUTED HOMOCHIRAL TETRAHYDROFURANS - Wheatley, J; Bichard, C; Mantell, S; Son, J; Hughes, D; Fleet, G; Brown, D (1993)
Excellent yields of methyl tetrahydrofuran-α-carboxylates are obtained by treatment of 2-O-trifluoromethanesulfonates (triflates) of either 1,4-or 1,5-lactones with acid in methanol; in some cases, very different tetrahydrofurans may result from acid or base treatment of a methanolic solution of the same starting material.